2012
DOI: 10.1097/tp.0b013e31824e7620
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Determinants, and Outcome of Chronic Kidney Disease After Adult Heart Transplantation in the United Kingdom

Abstract: CKD is a common complication of heart transplantation in the UK, and several risk factors identified in other studies are also relevant in this population. By linking national heart transplantation and renal data, we have determined the impact of CKD stage and dialysis treatment on subsequent survival in heart transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
6
38
3
Order By: Relevance
“…Indeed, renal failure after HTx is associated with significant mortality and morbidity . Ojo et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, renal failure after HTx is associated with significant mortality and morbidity . Ojo et al .…”
Section: Introductionmentioning
confidence: 99%
“…This gain in shortterm life expectancy, however, has increased awareness of the side effects associated with CNI-based immunosuppression and shifted attention toward strategies that could reduce long-term CNI-related morbidity (3). In particular, chronic renal failure occurs in approximately 11% of heart transplant recipients during the first 5 years posttransplant (4,5), and is associated with more than a fourfold increase in mortality (4). A major cause of renal injury, at least in the early posttransplant period, is CNIrelated nephrotoxicity (6).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Group 1 (non-overweight) had almost doubled the percentage of female patients as compared to Group 2 (29.6% vs 15.9%). Previous ISHLT registry reports, 1,9,39,40,42 as well as numerous other studies, 43–46,4952 have shown worse outcomes in female HT recipients in such areas as mortality, re-hospitalization, rejection, and renal dysfunction.…”
Section: Discussionmentioning
confidence: 86%